Estructura organizativa de los medios de comunicación digitales en la Provincia de Los Ríos 2023 - Casquete Mendoza, Diket Solange (2023)
Digital media refers to the formats through which it is possible to transmit or create information using digital platforms. These spaces encourage communication between users and content creators, to include all communicative practices that are carried out through digital technologies. With the objective of examining the organizational structure of digital media in the province of Los Ríos in the year 2023, a study was carried out that used a mixed approach, a non-experimental design and a descriptive and exploratory approach. Surveys were conducted with 30 digital media owners and the director of the digital newspaper Al Dia.com was interviewed to understand the dynamics of consolidation. The results revealed that 70% of these media lack a defined organizational structure, 40% consider that digital media exert a greater influence compared to traditional media. In terms of organizational structure, these media have seven main departments: Digital Director, Administrator, Network Coordinator, General Editor, Head of Production, Commercial Executive and Sales Manager, as well as Graphic Editor, 50% of the media have a seniority . of two years, 30% have between two and six employees in their structure. For the most part, the staff is made up of Social Communicators who work with responsibility and journalistic ethics. 55% of these media focus on the production of news related to political issues, 40% have a website, and 60% indicate that the organizational structure has a significant impact on the consolidation of the digital medium. In the province of Los Ríos, digital media are managed by Social Communicators, who obtain an audience by promoting their social networks; In order to maintain high standards of objectivity and impartiality, they verify information and offer balanced coverage of events.